2018
DOI: 10.11622/smedj.2018027
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the decision to pursue emergency medicine as a career among medical students in Singapore

Abstract: INTRODUCTIONThe emergency medicine (EM) residency programme was introduced in Singapore in 2010 as part of a nationwide effort by the Ministry of Health Holdings (MOHH) to improve existing postgraduate training systems across all medical and surgical specialties.(1,2) It is modelled after the American residency system and replaces the old specialty training programme, which involved rotating apprenticeships of varying duration with different governing bodies for employment, accreditation and evaluation of trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…19 While these studies are essential for programme directors of these specialties, it is not relevant to understanding what current medical students feel about the current medical education and healthcare trends. Factors found to affect the choice of specialty, and sponsoring institute in local studies 17,19 were largely similar to those found in overseas studies. 21 Some of these factors were seen to be important to students choosing a primary care career, and perhaps these factors could be highlighted specifically by faculties trying to encourage students towards a primary care career.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…19 While these studies are essential for programme directors of these specialties, it is not relevant to understanding what current medical students feel about the current medical education and healthcare trends. Factors found to affect the choice of specialty, and sponsoring institute in local studies 17,19 were largely similar to those found in overseas studies. 21 Some of these factors were seen to be important to students choosing a primary care career, and perhaps these factors could be highlighted specifically by faculties trying to encourage students towards a primary care career.…”
supporting
confidence: 61%
“…14 Deans of medical schools have even expressed concerns about the availability of residency training positions, 15 with some suggesting that these shortages would not have been present if the specialist residency programmes were not capped 30 years ago. 16 In Singapore, published studies are centered around what factors influence medical student choices for specific specialties like emergency medicine 17 and psychiatry, or focusing on the impact of a specific factor like debt on specialty choice, 18 or factors affecting the choice of a sponsoring institute. 19 While these studies are essential for programme directors of these specialties, it is not relevant to understanding what current medical students feel about the current medical education and healthcare trends.…”
mentioning
confidence: 99%
“…The components in PCA have then been used to compute Spearman correlation coefficients, and we have found that the importance of prestige positively but weakly correlates with the choice of EM, while it negatively but weakly correlates with the importance of work conditions. This is contrary to the Singaporean medical students, who had prestige (measured directly, unlike our study where we measured it through PCA) positioned as a negative factor of influence [ 66 ]. Age correlated negatively, which also translates to actual applications for EM residency in Slovenia [ 11 ].…”
Section: Discussionmentioning
confidence: 57%
“…Chew et al reported that focus on urgent care, salary, and exposure to elective EM training influenced junior students to seek EM as a career choice. Senior students were more likely to pursue EM due to exposure to elective EM training [14] .…”
Section: Discussionmentioning
confidence: 99%